Cancer 2015: a longitudinal whole-of-system study of genomic cancer medicine. Issue 12 (December 2015) - Thomas, David M.; Fox, Stephen; Lorgelly, Paula K.; Ashley, David; Richardson, Gary; Lipton, Lara; Parisot, John P.; Lucas, Mark; McNeil, John
Highlights: Cancer is a genetic disease, and genomic advances promise to revolutionise medicine. The impact on the health system is likely massive, and potentially costly, particularly in publicly funded health systems. The dominant focus to date is on use of genomic tools to more accurately select patients for molecular therapeutics. Cancer 2015 is a longitudinal cohort designed to assay the impact of genomic screening on personal and social outcomes for a broad range of cancers in the Australian community. Abstract : Genomic cancer medicine promises revolutionary change in oncology. The impacts of 'personalized medicine', based upon a molecular classification of cancer and linked to targeted therapies, will extend from individual patient outcomes to the health economy at large. To address the 'whole-of-system' impact of genomic cancer medicine, we have established a prospective cohort of patients with newly diagnosed cancer in the state of Victoria, Australia, about whom we have collected a broad range of clinical, demographic, molecular, and patient-reported data, as well as data on health resource utilization. Our goal is to create a model for investigating public investment in genomic medicine that maximizes the cost:benefit ratio for the Australian community at large.